1993
DOI: 10.1071/pp9930015
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Acquisition and Metabolism in a Root Hemiparasitic Angiosperm, Thesium humile (Santalaceae) Growing on Wheat (Triticum vulgare)

Abstract: Thesium humile Vahl (Santalaceae) is a root-hemiparasite which causes economic losses in cereal crops in the Mediterranean countries. O2 exchange measurements showed that photosynthesis does occur in Thesium. Experiments using 14CO2 gave additional evidence of the photosynthetic capacity of T. humile at both preparasitic and parasitic stages; roots of T. humile, unlike those of non-parasitic plants, exhibited a low sink strength for photosynthates. The end product of photosynthesis in T. humile is mannitol whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…While metabolic profiling in plants is increasing (Fiehn et al, 2000), such studies have not been carried out so far on a parasitic higher plant, and information on biochemistry remains poor in S. hermonthica. Nevertheless, most of the metabolic studies carried out on S. hermonthica and some other root parasites have focused on the specific trait of mannitol accumulation (Nour et al, 1984;Stewart et al, 1984;Wegmann, 1986;Press, 1989;Fer et al, 1993;Press, 1995;Pageau et al, 1998). Unlike the situation in the infested plants, mannitol is a key compound in physiology and carbon metabolism in these root parasites.…”
Section: Introductionmentioning
confidence: 99%
“…While metabolic profiling in plants is increasing (Fiehn et al, 2000), such studies have not been carried out so far on a parasitic higher plant, and information on biochemistry remains poor in S. hermonthica. Nevertheless, most of the metabolic studies carried out on S. hermonthica and some other root parasites have focused on the specific trait of mannitol accumulation (Nour et al, 1984;Stewart et al, 1984;Wegmann, 1986;Press, 1989;Fer et al, 1993;Press, 1995;Pageau et al, 1998). Unlike the situation in the infested plants, mannitol is a key compound in physiology and carbon metabolism in these root parasites.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the conclusions of Lawrence & Kaye (2008), who found higher survival of Castilleja levisecta in treatments without any host added. Similarly, Fer et al . (1993, 1994) suggested in their studies that T. humile Vahl is able to germinate in the absence of host chemical stimulants.…”
Section: Discussionmentioning
confidence: 68%
“…are well‐known agricultural weeds (e.g. Fer et al ., 1993), whereas others are endangered (e.g. T. ebracteatum , T. rostratum and T. arvense ; Holub & Procházka, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Years ago, I was able to maintain Gaiadendron punctatum alive and vigorous for nearly a year, after which an accident terminated the effort. Thesium humile is able to grow without host contact for 1-3 months following germination, although at a low level of photosynthesis (Fer et al 1993). I have not been able to find any information on seedling survival of any other Santalales except for Comandra (Piehl 1965a), where it seems to have several environmental constraints; Barber (as cited in Pilger 1935) speaks of more than a year for Santalum album.…”
Section: Haustoria In Santalalesmentioning
confidence: 98%
“…Santalum album shows superior growth performance and higher photosynthetic rates and foliar N concentrations when partnered with legumes rather than Eucalyptus. A different study was carried out by Fer et al (1993) on the parasitism of Thesium humile on Triticum, where it was shown that sucrose absorbed from the host is rapidly converted to mannitol. The latter also seems to be the end product of the parasite's own photosynthesis.…”
Section: Haustoria In Santalalesmentioning
confidence: 99%